Agribusiness market information via mobile phone one tool, many impacts - Ricau, Pierre; Tossou, Hermann S.; Osseni, Senou; Bappa Se, Marc Ghislain (Technical Centre for Agricultural and Rural Cooperation, 2018)
Market information service helps farmers improve decisions and raise incomes